Food production and agriculture - Branco, Patricia Alexandra Batista (Delve Publishing, 2020)
Food Production And Agriculture provides the readers with the basic information on the processes of food production and the rile of agriculture in it. It also talks about the factors that affect the agricultural food production and the relationship between the economic growth and food production. It provides the readers with deep insights into the various aspects related to the agriculture and the food production related to it for a deep understanding of the subject. This book also discusses about the animals used in agriculture and their production, the food crops that are generally used in agriculture and their production, the role played by water in irrigation and the nitrogen fertilizers in agricultural food production, the various effects of environmental factors and the role and significance of women in agriculture.